Manganese Dioxide As Rechargeable Magnesium Battery Cathode - Ling, Chen; Zhang, Ruigang (Frontiers in Energy Research, 2017)
Rechargeable magnesium battery (rMBs) has received increased attention as a promising alternative to current Li-ion technology. However, the lack of appropriate cathode that provides high energy density and good sustainability greatly hinders the development of practical rMBs. To date, the successful Mg2+-intercalation was only achieved in only a few cathode hosts, one of which is manganese dioxide. This Review summarizes the research activity of studying MnO2 in magnesium cells. In recent years the cathodic performance of MnO2 was impressively improved to the capacity of >150-200 mAh g-1 at voltage of 2.6-2.8 V with cyclability to hundreds or more cycles. In addition to reviewing electrochemical performance, we sketch a mechanistic picture to show how the fundamental understanding about MnO2 cathode has been changed and how it paved the road to the improvement of cathode performance.